The impact of climate change on birder destination loyalty: examining changes in bird resources. Issue 11 (3rd June 2022) - Li, Ningxin; Yang, Chen; Qin, Xinyue; Sun, Jingjing; Liu, Jun
ABSTRACT: Climate change has had a considerable impact on bird activities; however, it remains unclear how birders perceive the effects of climate change and whether their perceptions affect their loyalty to birding destinations. Based on the cognitive appraisal theory of emotions, this study constructs a destination loyalty model driven by the perception that bird resources have changed and place attachment of birders. We collected 252 valid questionnaires at five well-known birding destinations in China, including Baihualing in Yunnan, Nonggang in Guangxi, Chengdu in Sichuan, and Guangzhou and Shenzhen in Guangdong to test the proposed model. The study indicated four important findings. First, when climate change caused significant changes in bird migration time as perceived by birders, their loyalty to birding destinations was significantly reduced. Second, when mediated by place attachment, changes in bird migration time, population and distribution/habitat had negative impacts on loyalty to birding destinations. Third, the change in bird departure time had the greatest impact on birding destination loyalty. Finally, the change in bird distribution/habitat in a city had the greatest impact on place attachment than changes in migration time and population of birds. Specific theoretical and practical implications are provided.